Cancer: The Health Challenge of the New Millennium. - Md. Tahir Azhar (2001)
Life is a challenge and a constant struggle, a cliche perhaps, but ever so true. Written history is dotted with human struggles against dreaded diseases such as plague, syphilis, sleeping sickness, small pox, malaria, tuberculosis, leprosy, diptheria, polio and such infections which are now either eliminated or very much under control. Cancer on the other hand, a non infective affliction has been a challenge to human civilization and to this day remains so. Contrary to popular belief it is not a new disease. Indeed it is as old as written history itself.